Yield and quality of potato tubers when grown in organic farming conditions - Yu. P. Loginov; A. A. Kazak; A. S. Gayzatulin (Овощи России, 2023)
Methodology. The purpose of the research: to study the yield and quality of tubers of early ripe potato varieties Charoit and Meteor in organic farming in the northern forest-steppe of the Tyumen region. Studies were carried out in 2019- 2022 on the experimental field of the Northern Trans-Ural State Agricultural University. The soil of chernozem is leached, heavily carbonaceous in grain size distribution, medium provided with nitrogen and phosphorus, good – potassium, pH – 6.7 humus content – 7.2%. The content of trace elements in the soil is satisfactory. The precursor is spring wheat + rape per siderate. The green mass of the sideral culture (170 c/ha) was smelled on the fifth of October. In the spring, harrowing was carried out in order to retain moisture in the soil, then at a temperature of + 10…+12°C at a depth of 10-12 cm, milling, cutting of ridges and planting with sprouted tubers were carried out. The landing scheme is 75x30 cm, the plot area is 50 m2, the accounting one is 30 m2, the repetition is four times, the location of the plots is rendered. Prior to planting, tubers were treated with Taboo, 1 L/t and growth bioregulator Rostock, 0.5 L/t, and plants were treated with Immunocytophyte, 0.5 g/ha during the budding phase. Mineral fertilizers were not contributed. Caring for potato plantings included two interrow treatments and sinking.Results. It was established that in potato crop rotation with the annual use of sideral fertilizers, the yield of the noted varieties averaged 21.7-22.0 t/ha over four years, or 1.1-1.4 t/ha higher than the Zhukovsky early standard. The yield was combined with high quality tubers: starch content 13.9-14.6%, vitamin "C" 15.6-16.4 mg/%, nitrates – 59-81 mg/100 g, taste rating – 4.1-4.3 points.